Instructional Digital Leadership for Strengthening Technology-Responsive Digital Literacy and Ethical Learning Culture in Elementary Schools - Isharyanto, Isharyanto; Andriani, Dwi Esti (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Digital transformation in elementary education requires instructional leadership that extends beyond technology adoption to foster technology-responsive teaching practices, digital literacy, and an ethical learning culture. This study investigates how instructional digital leadership enacted by a school principal strengthens technology-responsive digital literacy and ethical learning culture in an elementary school setting. Employing an instrumental qualitative case study design, the research was conducted at SDN Ponggok, Pacitan, Indonesia. Data were collected through semi-structured interviews, passive participant observations, and document analysis involving the principal, teachers, educational practitioners, and students. The data were analyzed using within-case thematic analysis supported by source triangulation to ensure the credibility of the findings. The study identified four interconnected dimensions of instructional digital leadership: visionary articulator, teacher capability builder, resource organizer, and culture shaper. These leadership practices were implemented through a year-long technology-supported extracurricular program emphasizing digital citizenship, ethical internet use, project-based digital literacy activities, and collaborative learning experiences. The findings indicate that instructional digital leadership creates a supportive pedagogical ecosystem in which teachers are empowered to integrate technology into meaningful learning experiences while students develop responsible digital behaviors and ethical awareness. Despite challenges related to limited technological infrastructure and sustainable external partnerships, strong leadership commitment and teacher collaboration facilitated the successful implementation of technology-enhanced learning initiatives. This study contributes to the field of educational technology by demonstrating that instructional digital leadership serves as a strategic mechanism for integrating technology with pedagogy, strengthening teacher capacity, and cultivating a sustainable digital learning culture in elementary schools.